A study of atmospheric boundary layer characteristics with ground snow cover - numerical method (MAUSAM, 1997)
ABSTRACT. A one-dimensional version of a mesoscale model was used to simulate the atmospheric variables over ground snow cover after incorporating suitable modifications. Modifications to include the effect of cloud on shortwave and long wave radiation were also made in the model. The model takes into account both the heat balance at the snow surface and at various layers of the snow pack and calculates the melt rate in situ. Srinagar (Jammu & Kashmir) winter data was used for the simulations. The diurnal variation of snowmelt rate and other atmospheric variables were simulated simultaneously by the model. Melt rate values were verified with the values obtained from standard empirical formula. The model-simulated profiles of potential temperature, specific humidity and wind speed were found to be in reasonable agreement with available observations. The results were found to be insensitive to changes in surface drag coefficients.